Prospective randomized study of sexual function in men taking dutasteride for the treatment of androgenetic alopecia. Issue 7 (18th April 2018) - Tsai, Tsen‐Fang; Choi, Gwang Seong; Kim, Beom Joon; Kim, Moon‐Bum; Ng, Chi Fai; Kochhar, Puja; Jasper, Stacy; Brotherton, Betsy; Orban, Barbara; Lulic, Zrinka
Abstract: Treatment with 5α‐reductase inhibitors has been associated with sexual adverse events such as impotence (erectile dysfunction) and decreased libido. The primary objective of this study was to evaluate adverse events related to sexual function, based on their frequency, duration, persistence and associated treatment discontinuations, in men treated with dutasteride for androgenetic alopecia. Participants were randomized to receive double‐blind dutasteride 0.5 mg or placebo once daily for 24 weeks, followed by open‐label dutasteride 0.5 mg for an additional 24 weeks. Sexual adverse events were followed up until resolution or for up to 24 weeks after the last dose. Overall, 117 men, 23–50 years of age, were randomized. The incidence of sexual adverse events was approximately twofold higher in the dutasteride group (16%) than the placebo group (8%) during the double‐blind period; the overall incidence of sexual adverse events was lower (5%) during the open‐label period. All adverse events were mild to moderate in severity and considered treatment‐related. The adverse events resolved while on study treatment or after the end of treatment and did not lead to treatment discontinuation. A limitation of this study was the small sample size. The sexual adverse events of impotence, decreased libido and ejaculation disorders reported in this study were expected and reversible.